OP0309 Characterisation of clinical benefits in subjects classified as acr20 non-responders at week 104 of apremilast treatment: subanalysis of 3 long-term, phase iii trials. (12th June 2018) - Mease, P.; Gladman, D.; Kavanaugh, A.; Nakasato, P.; Guerette, B.; Teng, L.; Nash, P.
Abstract : Background: The PALACE 1, 2, and 3 trials evaluated the efficacy and safety of apremilast (APR) in subjects with active psoriatic arthritis (PsA) despite prior conventional disease-modifying anti-rheumatic drugs and/or biologics. Objectives: The aim of this analysis is to further characterise the clinical benefits associated with long-term APR exposure in subjects who failed to achieve an ACR20 response at Week 104. Methods: Subjects were randomised (1:1:1) to receive placebo (PBO), APR 30 mg BID (APR30), or APR 20 mg BID at baseline. Subjects who were randomised to APR30 at baseline and classified as ACR20 non-responders (ACR20NRs) at Week 104 were considered for this analysis. At Weeks 24, 52, and 104, ACR core components were examined as well as the proportions of subjects achieving PASI-75/PASI-50 among those with psoriasis involvement ≥3% of the body surface area at baseline, and dactylitis count and MASES of 0 among those with dactylitis or enthesitis at baseline. Safety is described for the overall PALACE 1–3 population. Results: A total of 109 subjects randomised to APR30 treatment at baseline were ACR20NRs at Week 104. Baseline ACR core components were similar for ACR20NRs and ACR20 responders at Week 104. Among these ACR20NRs, several core components of ACR response, including swollen/tender joint counts and Physician's Global Assessment of Disease Activity (visual analogue scale) scores, showed sustained improvements from baseline through Week 104 (table 1). Importantly, of the 109 ACR20NRs at Week 104, 50.0% achieved a PASI-50 response after continued treatment with APR30 through Week 104 (table 1). Among ACR20NRs with baseline dactylitis (n=44) or enthesitis (n=74), 68.2% achieved a dactylitis count of 0% and 33.8% achieved a MASES of 0 at Week 104. More limited improvements in Subject's Global Assessment of Disease Activity, Subject's Assessment of Pain, Health Assessment Questionnaire-Disability Index, and C-reactive protein outcomes most commonly had an impact on subjects' ability to achieve an ACR20 response. In the overall subject population, no new safety concerns were identified through 104 weeks. Conclusions: ACR20NRs receiving APR30 demonstrated significant improvements in core PsA domains. The data may explain why subjects who failed to achieve an ACR20 response remained on long-term APR treatment. These findings suggest that some subjects with PsA may experience meaningful clinical improvement that is not completely captured by the assessment of ACR20 response criteria. Outcome measures specifically designed for PsA subjects, may be more suitable to evaluate treatment response in PsA subjects. Disclosure of Interest: P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Genentech, Janssen, Eli Lilly, Pfizer, UCB, D. Gladman Grant/research support from: AbbVie, Amgen, BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB, Consultant for: AbbVie, Amgen, BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB, A. Kavanaugh Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Celgene Corporation, Centocor-Janssen, Pfizer, Roche, UCB, P. Nakasato Employee of: Celgene Corporation, B. Guerette Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, P. Nash Grant/research support from: Celgene Corporation